Testing a proposed paradigm shift in analysis of phage DNA packaging - Serwer, Philip (Bacteriophage, 2017)
We argue that a paradigm shift is needed in the analysis of phage DNA packaging. We then test a prediction of the following paradigm shift-engendering hypothesis. The motor of phage DNA packaging has two cycles: (1) the well-known packaging ATPase-driven (type 1) cycle and (2) a proposed back-up, shell expansion/contraction-driven (type 2) cycle that reverses type 1 cycle stalls by expelling accidentally packaged non-DNA molecules. We test the prediction that increasing the cellular concentration of all macromolecules will cause packaging-active capsids to divert to states of hyper-expansion and contraction. We use a directed evolution-derived, 3-site phage T3 mutant, adapted to propagation in concentrated bacterial cytoplasm. We find this prediction correct while discovering novel T3 capsids previously obscure.